Does COVID-19 Pandemic Crisis Affect CSR Costs? Case of Indonesia - Elisabeth Ria Viana Praningtyas; Rini Subekti; Putu Ayu Anggya Agustina (Journal of Accounting Auditing and Business, 2023)
The outbreak of COVID-19 that has been happening all around the world since early 2020 was a tough challenge for business entities. What was let down to keep the business alive was none other than sustainability performance, which is funded by CSR cost. This study examines the potential moderation effect of the COVID-19 pandemic crisis on the relationship between the company size and the current ratio of CSR costs, especially for developing countries. The data was collected from public companies listed on Indonesia Stock Exchange from 2019-2020. This study shows that regarding the size of the company, the commitment to fund CSR activities increases as the COVID-19 crisis hit. On the contrary, companies with high liquidity do not necessarily active in environmental action when the pandemic hit. This study's novelty is examining the COVID-19 Pandemic crisis as a moderating variable in studying business entity behaviour towards their CSR. Besides, this study gives elaboration on what happened in Indonesia, one of the developing countries that suffered from the COVID-19 pandemic crisis.